FLASH FICTION AS AN INNOVATION IN LYDIA DAVIS’S SHORT STORIES - Mirmuhsin Yuldashev Munavvarjon o’gli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The author of this thesis reviews the genre of flash fiction in Lydia Davis’s works. The thesis covers a wide determination of the term flash fiction and gives an explanation Lydia Davis’s flash fiction style in her short stories with textual examples, taken from short stories of Lydia Davis. She has 5 books of collections of stories. Her stories are extremely short even some of her stories consist of several words. This paper also tries to place Lydia Davis as a great example of flash fiction within Modern American short story genre. Totally, this thesis studies short stories of Lydia Davis on the characteristics of selected stories from her books which depict the categorization of her stories.